1995
DOI: 10.1300/j069v13n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Therapist/Patient Matching and Early Treatment Dropout

Abstract: This study of intake procedures was initiated with a view towards reducing the early dropout rate of substance abusers. Eight different therapists conducted intake interviews of 634 cocaine dependent, first admissions to an outpatient cocaine treatment program. No significant differences in return rate were found across either the eight therapists or their level of academic training. We found that matching therapists and patients with respect to gender and race for the intake interview did not increase the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Unfortunately, the contradictory findings of the few existing studies addressing this question do not allow such a recommendation. Some studies find that similarity between therapist and patient on variables such as age, race, gender, and sexual orientation has a positive influence on treatment outcome (Beane 1981;Gardner 1971;Griffith, and Jones 1978;Luborsky, Chandler, Auerbach, Cohen, and Auerbach 1971), but other studies do not corroborate these findings (Atkinson and Schein 1986;Gottheil, Sterling, Weinstein and Kurtz 1994;Sue 1988).…”
Section: The Promise Of Gender and Ethnic Congruencymentioning
confidence: 99%
“…Unfortunately, the contradictory findings of the few existing studies addressing this question do not allow such a recommendation. Some studies find that similarity between therapist and patient on variables such as age, race, gender, and sexual orientation has a positive influence on treatment outcome (Beane 1981;Gardner 1971;Griffith, and Jones 1978;Luborsky, Chandler, Auerbach, Cohen, and Auerbach 1971), but other studies do not corroborate these findings (Atkinson and Schein 1986;Gottheil, Sterling, Weinstein and Kurtz 1994;Sue 1988).…”
Section: The Promise Of Gender and Ethnic Congruencymentioning
confidence: 99%
“…In the USA it is estimated that 125,000 deaths, hundreds of thousands of hospitalisations, and ixiillions of working days lost, result from non-compliance. In recent years this phenomenon has been included in the general framework of the doctor/ patient relationship (Meise et al 1992; Gottheil et al 1994;Steiner & Vetter, 1994;Spaeth, 1995), losing its pejorative nature (Holm, 1993;Dunbar-Jacob, 1993;Cohen, 1993;Diamond & Factor, 1994) and acquiring a non-punitive nuance, to be viewed as a reasoned action on the part of the patient (Donovan & Blake, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Although CS intervention studies tend to match participants and research staff racially, empirical evidence for a positive effect on outcomes is limited. Indeed, previous research has found that gender and race matching does not improve retention or outcomes (Gottheil, Sterling, Weinstein, & Kurtz, 1994;Sterling, Gottheil, Weinstein, & Serota, 1998;Striley, Margavio, & Cottler, 2006). This group of participants also expressed concerns regarding possible discrimination or inequity in treatment quality due to a focus on culture and race.…”
Section: Discussionmentioning
confidence: 99%